2018
DOI: 10.21873/invivo.11265
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Matrix Metalloproteinase-1 Promoter Polymorphisms with Breast Cancer

Abstract: Abstract. Background For many years, breast cancer has been the most common malignancy and the leading cause of female cancer mortality all over the world (1). According to the most updated report about burden of disease trends, cancers overall have increased by 34% during 199-2015 while breast cancer related deaths globally have increased to 45%, a much higher level than average overall cancers (1). In Taiwan, breast cancer has the highest incidence and is ranked as the fourth leading cause of mortality among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The following supporting information can be downloaded at: . References [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…In a meta-analysis investigating more than 38,000 subjects, the results also indicated that the genotypes of MMP-1 rs1799750 may be associated with colorectal, head and neck and renal cancer risk (31). However, in other types of cancers, the genotypes of MMP-1 rs1799750 may not directly contribute to susceptibility determination (17,(32)(33)(34)(35), which indicated that the MMP-1 rs1799750 genotypes may be indirectly involved in carcinogenesis. The detailed mechanisms of how MMP-1 rs1799750 genotypes interact with other molecules leading to CRC need further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, associations of MMP1 genotypes have been examined among many types of cancer, such as lung (32,33), breast (34)(35)(36), oral (37), colorectal (38,39), gastric (40)(41)(42), endometrial (43), cervical (44,45), prostate (17,46), and ovarian (47,48), in addition to bladder cancer (49)(50)(51)(52). Although there were several studies investigating the association of MMP1 genotypes with bladder cancer, the results were inconclusive and the total sample size is far from convincing, which we discuss later.…”
Section: Discussionmentioning
confidence: 99%